European Union law - Margot Horspool (Oxford University Press, 2006)
European Union Law provides students with a clear understanding of the law of the European Union and the fundamental principles that support it. This revised and updated edition offers essential information in a user-friendly format to facilitate learning and understanding of this key discipline